2022
DOI: 10.1007/s40620-022-01413-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the efficacy and safety of anticoagulants in advanced chronic kidney disease

Abstract: Background Patients with chronic kidney disease (CKD) have an increased risk of venous thromboembolism (VTE) and atrial fibrillation (AF). Anticoagulants have not been studied in randomised controlled trials with CrCl < 30 ml/min. The objective of this review was to identify the impact of different anticoagulant strategies in patients with advanced CKD including dialysis. Methods We conducted a systematic review of randomized controlled trials and cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…For patients with CKD stage 5 and on dialysis, most respondents would use VKAs which is likely due to a lack of licensing and limited published evidence for DOACs in this scenario. Apixaban was the DOAC selected by all respondents when used in CKD stage 5 and dialysis and this may be based on the findings of a number of observational studies and a recent systematic review from our group which showed apixaban had a lower risk of bleeding compared to warfarin [9,[39][40][41][42][43][44]. However, more evidence is needed to support the use of DOACs in the treatment of VTE in patients with CKD stage 5 and dialysis.…”
Section: Treatment Of Vtementioning
confidence: 99%
See 2 more Smart Citations
“…For patients with CKD stage 5 and on dialysis, most respondents would use VKAs which is likely due to a lack of licensing and limited published evidence for DOACs in this scenario. Apixaban was the DOAC selected by all respondents when used in CKD stage 5 and dialysis and this may be based on the findings of a number of observational studies and a recent systematic review from our group which showed apixaban had a lower risk of bleeding compared to warfarin [9,[39][40][41][42][43][44]. However, more evidence is needed to support the use of DOACs in the treatment of VTE in patients with CKD stage 5 and dialysis.…”
Section: Treatment Of Vtementioning
confidence: 99%
“…One in ten respondents did not use any risk scores and this may relate to their lack of validation in patients with advanced CKD [50,51]. Respondents were less likely to anticoagulate patients on dialysis which may relate to the uncertainty in whether anticoagulation reduces the risk of stroke in this group [9,52]. The use of anticoagulants versus no anticoagulation in dialysis patients with AF is currently being investigated in a number of RCTs [53][54][55].…”
Section: Anticoagulation In Afmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with CKD stage 5 and on dialysis, most respondents would use VKAs which is likely due to a lack of licensing and limited published evidence for DOACs in this scenario. Apixaban was the DOAC selected by all respondents when used in CKD stage 5 and dialysis and this may be based on the ndings of a number of observational studies and a recent systematic review from our group which showed apixaban had a lower risk of bleeding compared to warfarin (9,(39)(40)(41)(42)(43)(44). However, more evidence is needed to support the use of DOACs in the treatment of VTE in patients with CKD stage 5 and dialysis.…”
Section: Treatment Of Vtementioning
confidence: 99%
“…Thromboembolic events with AF can be reduced with the prescription of oral anticoagulants, which includes the vitamin K antagonists (VKAs) and direct oral acting anticoagulants (DOACs)(8). However, the bene ts of these agents are uncertain in advanced CKD due to an associated increased risk of bleeding (9), related to uraemia-induced platelet dysfunction and an increase in gastric angiodysplasias (10,11).…”
Section: Introductionmentioning
confidence: 99%